Conservative behavior of Mg isotopes in dolomite during diagenesis and hydrothermal alteration: A case study in the Lower Cambrian Qiulitage Formation, Gucheng area, Tarim Basin. (January 2023) - Li, Xi; Zhu, Guangyou; Li, Tingting; Zhou, Lei; Wu, Yuxuan; Shen, Bing; Ning, Meng
Abstract: Recovering the Mg isotopic composition of seawater using penecontemporaneous dolomite is possible; however, the Mg isotopic composition of dolomite may be changed by later diagenesis and hydrothermal activities. Solving this problem requires further research on the behavior of Mg isotopes in dolomitization systems. Diagenesis and hydrothermal fluids have significantly altered the considerable amount of dolomites in the Lower Cambrian Qiulitage Formation in the Gucheng region of the Tarim Basin. Thus, this formation is excellent for examining the behavior of dolomite Mg isotopes after diagnostic and hydrothermal alterations. The results of major and trace elements and C–O–Mg isotope analysis show that the dolomite of Qiulitage Formation is penecontemporaneous dolomite, and the Mg in dolomite is mainly from the Early Cambrian seawater. The dolomites of the Qiulitage Formation in the Gucheng area are formed by carbonate platform facies. The stratigraphic variability of Mg isotopes is small, averaging −2.08‰± 0.23‰, which indicates that the Mg isotope of the dolomitized fluid in the large-scale dolomitization process of the carbonate platform is uniform and balanced with the seawater in the same period. In addition, the Mg isotopic composition of dolomite is stable, and the δ 26 Mg value is not affected by burial diagenesis and hydrothermal fluid activities. we found that the Mg isotopic composition and stratigraphic age of the dolomites of the Lower Cambrian Qiulitage Formation are consistent with the simulated results, the δ 26 Mg value of the ancient seawater in the Early Cambrian is estimated to be about −0.08‰±0.23‰. This study shows that the δ 26 Mg of penecontemporaneous massive dolomite may have been used to invert the Mg isotopic composition of seawater during the same period, within a confidence range of ±0.2‰, using massive dolomite, and provided a new idea for quantitatively reconstructing the marine Mg cycle in the geological history. Highlights: The penecontemporaneous dolomite can be used as an effective indicator of Mg isotopic composition of paleoseawater. Mg isotopes of dolomite are not affected by later burial diagenesis and hydrothermal activity. The δ 26 Mg value of the Early Cambrian seawater is about -0.08 ‰ ± 0.23‰.